Assessment of the potential for hydrokinetic energy production in the Douro river estuary under sea level rise scenarios. (15th May 2023) - Cruz, M.; Henriques, R.; Pinho, J.L.; Avilez-Valente, P.; Bio, A.; Iglesias, I.
Abstract: For being densely populated and urbanized, and for concentrating high-value economic activities, estuarine regions have an increased energy demand, which boosts the claim for new, efficient, renewable, and safe energy production. Among these technologies, hydrokinetic energy conversion systems are potentially well-suited for estuaries. However, in the actual context of climate change, it is important to know how changes in mean sea level may affect hydrokinetic energy production. This work proposes a methodology to assess the hydrokinetic energy potential for future scenarios using numerical hydrodynamic modeling techniques. Applied to the Douro estuary, several scenarios considering present conditions, as well as medium (2050) and long-term (2100) predictions under different Shared Socioeconomic Pathways are proposed. The results revealed that the studied region maintains a high dependence on freshwater discharge until 2100, although tidal oscillation is also significantly perceived in the entire estuary. Overall, hydrokinetic power potential will not increase with the mean sea level rise and will instead be considerably lower. Therefore, a decline in the kinetic energy available for exploitation is expected with increasing CO2 emissions, along with the associated intensification of sea level rise. Results reinforce the need to perform local studies to evaluate future trends in hydrokinetic energy production. Highlights: Numerical models are essential tools to represent the main forcings in estuaries. Combined effects of tide and river flow increase the hydrokinetic energy production. Hydrokinetic power potential will be considerably lower with the mean sea level rise in climate change scenarios. Local studies need to be performed to evaluate future trends in hydrokinetic energy exploitation.